META-ANALYSIS OF DIETARY SUNFLOWER OIL SUPPLEMENTATION FOR DAIRY GOATS: PERFORMANCE, MILK COMPOSITION, AND MILK FATTY ACID PROFILE - Darabighane, Badak; Ghavipanje, Navid; Robles Jimenez, Lizbeth E.; González-Ronquillo, Manuel; Vargas-Bello-Pérez, Einar (Chilean Journal of Agricultural & Animal Sciences, 2024)
Milk and dairy products are important foods that contribute to daily nutrient requirements and improve consumers’ health. The objectives of this study were to critically review and quantify, using meta-analysis and meta-regression, the effects of supplementation with sunflower oil (SFO) on dry matter intake (DMI), milk yield (MY), components and fatty acids (FAs) profile in dairy goats. A total of 154 papers were reviewed. Nine articles (10 experiments) met the eligibility criteria and were used in the analysis. The effect size for all parameters was calculated as raw mean difference (RMD) and standardized mean difference (SMD). Heterogeneity was determined using I2 statistics, while meta-regression was used to examine factors influencing heterogeneity. Responses to SFO supplementation were heterogeneous for all variables studied. However, SFO decreased DMI (RMD = -0.050 kg / d; p = 0.007) and increased milk fat percent (MFP; p < 0.001) and milk lactose percent (MLP; p < 0.001), but the effect size was not significant for MY. The inclusion of SFO in dairy goats rations enhanced C18:1 cis-9 (RMD = +2.22 g / 100 g FA; p < 0.001), C18:1 trans-11 (RMD = +2.77 g / 100 g FA; p < 0.001), C18:2 cis-9 trans-11 (RMD = +0.261 g / 100 g FA; p < 0.001), C18:3 n-3 (RMD = +0.078 g / 100 g FA; p = 0.002) and MUFA (RMD = +7.16 g / 100 g FA; p = 0.002) and PUFA (RMD = +1.49 g / 100 g FA; p < 0.0001), and diminished SFA (RMD = -7.53 g / 100 g FA; p = 0.008). Overall, the meta-analysis data indicated that dietary SFO supplementation in dairy goats has a positive effect on desirable milk components for human consumption. However, a cost-effectiveness analysis is needed to provide accurate recommendations to farmers and the dairy goat industry.